2011
DOI: 10.1016/j.eurpsy.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, characteristics and comorbidities of anxiety disorders in France: Results from the “Mental Health in General Population” Survey (MHGP)

Abstract: The MHGP study showed that anxiety disorders are highly prevalent in France with a high frequency of comorbidities. Our results highlight the need for considering anxiety disorders as a public health priority in France as well as in other European countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
4
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 30 publications
5
41
4
3
Order By: Relevance
“…This investigation demonstrated that the prevalence of current PTSD in young adults is in accordance with the parameters estimated in literature 14,15 . The prevalence of PTSD was higher amongst women and individuals who lived with a partner.…”
Section: Discussionsupporting
confidence: 71%
“…This investigation demonstrated that the prevalence of current PTSD in young adults is in accordance with the parameters estimated in literature 14,15 . The prevalence of PTSD was higher amongst women and individuals who lived with a partner.…”
Section: Discussionsupporting
confidence: 71%
“…These findings support the results of other studies on comorbid anxiety and depression. 3,7,12,[31][32][33][34][35] Therefore, health professionals encountering individuals with either anxiety or depressive symptoms should carefully assess for the presence of comorbid psychological conditions. In addition, considering that nearly 70% of those with comorbid GAD and MDE had at least one physical chronic condition, and in light of solid evidence elucidating the bidirectional relationship between mental illnesses (specifically depression and anxiety) and physical health outcomes, 36 particular attention should be given to the prevention Furthermore, this paper demonstrated that nearly 50% of those with comorbid GAD and MDE perceived that their need for mental health care was either not met or only partially met compared to about 30% of those with GAD only or MDE only.…”
Section: Discussionmentioning
confidence: 99%
“…Leray et al [ anxiety disorders in adult French population was estimated to be 21.6 and 3.7% of individuals with a diagnosis of an anxiety disorders also met criteria for drug addiction [9]. In a recent population-based study from Denmark, Toftdahl et al established prevalence rates of SUDs in patients with anxiety disorders, postraumatic stress disorder (PTSD) and obsessive-compulsive disorders (OCD) as 24.8, 17 and 11.4%, respectively [10].…”
Section: Diagnostic Tools Resultsmentioning
confidence: 99%